Cultural Heritage in Music Teaching: the Experience in Croatia - Mucić, Mia; Berbić Kolar, Emina (Revija za elementarno izobraževanje, 2024)
This study explores music teachers’ attitudes toward cultural heritage education and to what extent this subject matter is implemented in music lessons. The study included music teachers (N = 61) employed in Croatian elementary schools. The results show that music teachers have a very positive attitude towards the inclusion of cultural heritage education in music teaching and that music teachers believe such resources should be part of the music curriculum. The findings also show that some dissatisfaction is present among music teachers regarding the way such topics are presented in the music curriculum and their overall representation in music lessons.
Keywords: cultural heritage education, music curriculum, music teaching, music teacher.